Dziewczęta-żołnierze. Przyczyny występowania tego zjawiska - BŁAŻEJEWSKA, BEATA (Annales Missiologici Posnanienses, 2010)
This article presents an overview of the issue of the girls-soldiers. It presents the motives for becoming a soldiers by girls. Sometimes the reasons for becoming a soldier could be of fear (lack of safety), but often it is also of prestige and certain power. It might be surprising but a girl becoming a soldier may also gain some security or prestige.